Integrated co-fired inductor and its manufacturing method
The integrally co-fired inductor manufacturing method addresses the size and efficiency issues of conventional inductors by using coated magnetic powders and heat treatment, resulting in a compact, efficient, and stable inductor with reduced losses and improved yield.
Patent Information
- Application Number
- JP2023534000
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-04
- Filing Date
- 2021-11-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-11-24
AI Technical Summary
Conventional inductors used in high-frequency, high-current applications are large in size due to the need for an air gap and assembly of multiple parts, leading to increased material hysteresis losses, deformation, and inefficiencies in manufacturing yield.
An integrally co-fired inductor manufacturing method involving the use of magnetic powder with different types of insulation coatings and granulation processes, followed by hot or cold pressing and heat treatment, eliminates the assembly process and ensures uniform air gaps, reducing material hysteresis losses and deformation.
The method results in a smaller, more efficient inductor with reduced material hysteresis losses, even air gaps, and improved temperature stability, enhancing performance and manufacturing yield.
Smart Images

Figure 0007607772000001 
Figure 0007607772000002 
Figure 0007607772000003
Abstract
Description
[Technical field]
[0001] The present application belongs to the technical field of inductors, and relates to an integral co-fired inductor and a manufacturing method thereof. [Background technology]
[0002] In recent years, with the large-scale use of equipment such as mobile devices, home appliances, automobiles, industrial equipment, data center servers, and communication base station servers, energy consumption has become an important consideration. The miniaturization, multi-function, high performance, and power saving of components are increasingly developed, and the mounted electronic elements are further required to be smaller / thinner and higher performance. Improving the efficiency of DC-DC converters and reducing heat generation are important conditions for the miniaturization of electronic elements. In particular, with the further development of high-speed conversion of DC-DC converter ICs and low impedance of the inductors used, the core power circuit is increasingly required to be smaller / thinner, low DC impedance, high current support, and high reliability.
[0003] At present, the use of third-generation semiconductors in power devices is gradually becoming mainstream. In particular, the technologies of gallium nitride (GaN) and silicon carbide (SiC) are relatively mature and are applied to high-frequency power devices that can withstand high temperatures, high voltages, and large currents. Among them, power semiconductors are the main field of use. Gallium nitride has prominent advantages in high-frequency circuits and is a strong competitor in current mobile communications. At present, the main operating scenarios are mainly concentrated in the power amplifiers on the base station side, aerospace and other military fields, and at the same time, it is gradually shifting to the consumer electronics field. Due to its high output power and high energy efficiency characteristics, it can achieve a smaller volume at a given power level, so it can be used in power supply fast charging products. The physical performance of silicon carbide materials is superior to materials such as silicon. The forbidden band width of silicon carbide single crystal is about three times that of silicon materials, the thermal conductivity is 3.3 times that of silicon materials, the electron saturation transfer speed is 2.5 times that of silicon, and the breakdown field strength is five times that of silicon, which has irreplaceable advantages in high-temperature, high-voltage, high-frequency, and high-power electronic devices. With the successful implementation of silicon carbide power semiconductors in premium automobile markets such as Tesla, the automotive sector will be the main driver of silicon carbide growth in the future.
[0004] Power semiconductors are the core of electrical energy conversion and circuit control in electronic devices, and are key components that realize functions such as voltage, frequency, and DC-AC conversion in electronic devices. Power ICs, IGBTs, MOSFETs, and diodes are the four most widely used power semiconductor products. Electronic elements / devices such as inductors and capacitors that work with power semiconductors to improve the electrical energy conversion efficiency of power supplies also need to keep up with the development trend of third-generation semiconductors. Inductors with high frequency, large current, high saturation current, and high reliability are also necessary components of energy-efficient power supplies.
[0005] Conventional inductors that can withstand high currents generally use soft magnetic materials as separate components, then place the coil on the magnetic core, and design an air gap to achieve high saturation superimposition current in the inductor device. This type of inductor needs to open and organize the air gap, so it tends to be large in size, especially in the thickness direction, which often exceeds 3mm and even reaches 7mm. This is due to the characteristics of the soft ferrite material itself, which has high permeability but low saturation magnetic flux density and is easily saturated by external magnetic fields, so in order to increase the ability to withstand saturation current, it is necessary to reduce the effective permeability by opening an air gap. The added air gap increases the size of the device and requires assembly and tolerance in the manufacturing process, which has a certain impact on the product manufacturing yield.
[0006] Metal powder core materials have been rapidly developed in recent years due to their characteristics such as high saturation magnetic flux density, high temperature stability, impact resistance, and low noise, and the use of metal soft magnetic materials such as FeSiCr, carbonyl iron, and iron-nickel has made great progress especially in the field of integrally molded inductors. Integral molded inductors use metal soft magnetic materials and place a coil on a metal powder core to form an integral structure.
[0007] CN205230770U discloses a vertical thin high current inductor, which includes an upper core, a lower core, and an inductor disposed between the upper core and the lower core, and the inductor is wound with a flat metal copper wire, and the upper and lower two flat pins extending from the inductor are bent at 90 degrees, and the directions of the two flat pins are opposite to each other, the upper core is a rectangular body, the lower core is provided with a groove for receiving the inductor, and a positioning post is provided in the middle of the groove for fixing the inductor. Such an inductor element requires the coil to be made of enameled wire for winding, so that the molding pressure is not likely to be large, otherwise the insulation layer of the coil is easily damaged and causes interlayer short circuit. Secondly, the stress caused by the molding pressure generates stress anisotropy in the core material, which increases the hysteresis loss of the material. In light of this, DUI-type inductor products have also been developed in which a metal powder core is divided into a U-piece and an I-piece, and after the powder core is sintered, a flat copper wire is sandwiched between them to assemble the inductor.
[0008] CN110718359A discloses a manufacturing structure and method for a surface mount integrally molded inductor, in which two sets of identical platen bodies are preformed using a mixture of magnetic powder and thermosetting resin, and the platen bodies have press surfaces, which are specifically higher on both sides and lower in the center. In the molding die, the two sets of platen bodies are respectively arranged directly above and below the built-in coil, the press surfaces of the platen bodies face the built-in coil, and both poles of the built-in coil must exceed the range of both ends of the platen bodies, respectively, and the two sets of platen bodies and the built-in coil are integrally molded into the material by pressure and / or heat. After molding, both poles of the built-in coil are exposed to the outside of the material, and external electrodes are formed on both ends of the material.
[0009] However, inductors made in this way require several parts to be assembled together, which tends to introduce an extra air gap between the coil and the magnetic core, reducing the effective permeability. In addition, some parts need to be made into thin sheets, which means the molding precision of the product is insufficient and polishing is required, which increases the process cost and reduces the product yield. Summary of the Invention
[0010] The following is a summary of the subject matter described in detail herein, which is not intended to limit the scope of protection of the claims.
[0011] In response to the deficiencies in the prior art, the objective of the present application is to provide an integrally co-fired inductor and a manufacturing method thereof, in which the manufacturing method of the present application uses an integral molding process to manufacture the inductor, avoiding the assembly process of excessive parts, and heat treating after integral molding to fully release stress and reduce the hysteresis loss of the material, so that the loss of the device is reduced under light load conditions, thereby eliminating excess gaps between the conductor and the magnetic core, and uniformly distributing the air gaps in the magnetic core, thereby reducing the vibration noise of eddy current losses.
[0012] To achieve this objective, the present application adopts the following technical proposal. In a first aspect, the present application provides a method for manufacturing an integral co-fired inductor, the method comprising: The method includes filling a cavity with magnetic powder in a batch, the magnetic powder in two adjacent layers being of different types, embedding at least one conductor in the magnetic powder in one of the layers, with both ends of the conductor extending from the cavity, and then sequentially pressing and heat treating the magnetic core to obtain the conductor extending from the magnetic core, bending the conductor extending from the magnetic core, and tin-plating the conductor to obtain the co-fired inductor.
[0013] The manufacturing method of the present application uses a one-piece molding process to manufacture the inductor, avoiding the assembly process of too many parts, and heat treatment after one-piece molding to fully release stress and reduce the hysteresis loss of the material, and in the light load state, the loss of the device is reduced, there is no extra gap between the conductor and the magnetic core, and the air gap is uniformly distributed in the magnetic core, reducing the vibration noise of the eddy current loss. In addition, in the pressing process, different powders are added in a multi-batch addition manner to minimize the deformation of the conductor during the pressing process, improve the anti-windup ability of the magnetic core material, fully exert the respective advantages of different magnetic powder materials, and better exert the characteristics of the device, and the combination of soft magnetic materials with positive and negative temperature coefficients can effectively improve the temperature stability of the device.
[0014] In the preferred technical solution of the present application, the magnetic powder is produced by a method in which soft magnetic powder is successively subjected to insulating coating, secondary coating and granulation to obtain the magnetic powder.
[0015] Preferably, the soft magnetic powder comprises FeSiCr, FeSi, FeNi, FeSiAl, carbonyl iron powder, carbonyl iron nickel powder, FeNiMo, Fe-based amorphous nanocrystalline material, Co-based amorphous nanocrystalline soft magnetic material or Ni-based amorphous nanocrystalline soft magnetic material.
[0016] As a preferred technical solution of the present application, the coating process used in the insulating coating includes phosphorization, acidification, oxidation or nitridation, and more preferably, phosphorization is used to insulate the soft magnetic powder.
[0017] The insulating coating process in this application refers to a coating process of a metal soft magnetic material that improves the insulating property and corrosion resistance of the surface of the metal soft magnetic powder, including surface treatments such as phosphorization, acidification, gradual oxidation, nitriding, etc., and mainly improves the insulation between the metal soft magnetic powders by adding high resistivity powder materials or growing in-situ a high resistivity coating layer including materials such as silica, alumina, magnesium oxide, kaolin, zirconia, mica powder, etc. on the surface of the metal soft magnetic particles. Different types of metal soft magnetic alloy powders need different coating methods and coating processes to achieve the best coating effect.
[0018] Preferably, said phosphoridation treatment comprises mixing the soft magnetic powder with diluted phosphoric acid, stirring and baking to obtain a phosphoridized soft magnetic powder.
[0019] Preferably, acetone is used to dilute the phosphoric acid.
[0020] Preferably, the mass ratio of phosphoric acid to acetone is 1:(60 to 70), and may be, for example, 1:60, 1:61, 1:62, 1:63, 1:64, 1:65, 1:66, 1:67, 1:68, 1:69, or 1:70, but is not limited to the recited numerical values, and other unrecited numerical values within the numerical range also apply.
[0021] Preferably, the phosphoric acid and acetone are mixed and stirred for 1 to 6 minutes, which may be, for example, 1 min, 2 min, 3 min, 4 min, 5 min, or 6 min, and then allowed to stand for 5 to 10 minutes in preparation for use, which may be, for example, 5 min, 6 min, 7 min, 8 min, 9 min, or 10 min, but are not limited to the recited values, and other unrecited values within the range of values also apply.
[0022] Preferably, the soft magnetic powder and diluted phosphoric acid are mixed and stirred for 30 to 60 minutes, which may be, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, but is not limited to the recited numerical values, and other unrecited numerical values within the numerical range also apply.
[0023] Preferably, the bake temperature is 90 to 110°C, and may be, for example, 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, 103°C, 104°C, 106°C, 108°C, or 110°C, but is not limited to the recited values, and other unrecited values within the numerical range apply as well.
[0024] Preferably, the bake time is 1 to 1.5 h, and may be, for example, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, or 1.5 h, but is not limited to the recited values, and other unrecited values within the range apply as well.
[0025] In the preferred technical solution of the present application, the secondary coating includes mixing and stirring the coating material and the insulating coated soft magnetic powder.
[0026] Preferably, the coating material is 2-10 wt% of the soft magnetic powder, and may be, for example, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt% or 10 wt%, but is not limited to the listed values, and other unlisted values within the range apply as well.
[0027] Preferably, the coating material comprises a phenolic resin, an epoxy resin or a silicone resin.
[0028] Preferably, the coating material and the soft magnetic powder are mixed and stirred for 40 to 60 minutes, which may be, for example, 40 min, 42 min, 44 min, 46 min, 48 min, 50 min, 52 min, 54 min, 56 min, 58 min or 60 min, but is not limited to the listed numerical values, and other unlisted numerical values within the numerical range also apply.
[0029] In the preferred technical solution of the present application, the granulation process includes granulating the secondary coated soft magnetic powder, and then drying, drying and cooling the powder after the granulation is completed to obtain the magnetic powder.
[0030] Preferably, the granulation process is carried out using a 40 to 60 mesh granulator, and may be, for example, 40 mesh, 42 mesh, 44 mesh, 46 mesh, 48 mesh, 50 mesh, 52 mesh, 54 mesh, 56 mesh, 58 mesh, or 60 mesh, but is not limited to the recited numerical values, and other unrecited numerical values within the numerical range also apply.
[0031] Preferably, the drying time is ≦3 h, and may be, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the recited values, and other unrecited values within the numerical range apply as well.
[0032] Preferably, the dried soft magnetic powder is sieved through a 30 to 50 mesh sieve and then dried, and may be, for example, 30 mesh, 32 mesh, 34 mesh, 36 mesh, 38 mesh, 40 mesh, 42 mesh, 44 mesh, 46 mesh, 48 mesh or 50 mesh, but is not limited to the listed numerical values, and other unlisted numerical values within the numerical range also apply.
[0033] Preferably, the drying temperature is 50 to 70°C, and may be, for example, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C or 70°C, but is not limited to the recited values, and other unrecited values within the numerical range apply as well.
[0034] Preferably, the drying time is 0.8 to 1.2 h, and may be, for example, 0.8 h, 0.9 h, 1.0 h, 1.1 h or 1.2 h, but is not limited to the recited values, and other unrecited values within the range apply as well.
[0035] Preferably, the cooling process is natural cooling.
[0036] Preferably, the cooled soft magnetic powder is sieved through a 30 to 50 mesh sieve, and then auxiliary raw materials are added to the sieved soft magnetic powder to obtain the magnetic powder. The sieved sieve may be, for example, 30 mesh, 32 mesh, 34 mesh, 36 mesh, 38 mesh, 40 mesh, 42 mesh, 44 mesh, 46 mesh, 48 mesh, or 50 mesh, but is not limited to the listed numerical values, and other unlisted numerical values within the numerical range also apply.
[0037] Preferably, the auxiliary raw materials include magnesium oxide, lubricant powder or release powder.
[0038] In a preferred technical solution of the present application, the first magnetic powder, the second magnetic powder, and the first magnetic powder are sequentially filled into the cavity for each of the three batches.
[0039] Preferably, the conductive wire is embedded in a second magnetic powder.
[0040] In a preferred technical solution of the present application, the conductor wire is a bare wire without an enameled wire.
[0041] Preferably, the conductor wire is a copper wire.
[0042] Preferably, the conductor is a flat conductor having a rectangular cross section.
[0043] Preferably, the conductor wire is a straight conductor wire or a shaped conductor wire.
[0044] Preferably, the shape of the irregular conductor includes an S-shape, an L-shape, a U-shape, a W-shape or an E-shape.
[0045] Preferably, the conductor wires are arranged side by side on a horizontal plane at intervals within one layer of magnetic powder.
[0046] The inductor designed in this application requires low DC resistance, and the copper wire must be subjected to high-temperature heat treatment together with the metal soft magnetic material, and a flat copper wire without enameled wire can be used for high-temperature heat treatment to further reduce the loss of the powder core, and the shape of the copper wire can be designed according to need, including I-shape, S-shape, L-shape, U-shape, W-shape, E-shape, etc. A one-piece molding process may be used, or in-line press molding may be performed in the form of a lead frame fixed.
[0047] In the preferred technical solution of the present application, the pressing method is hot pressing or cold pressing.
[0048] According to the characteristics of the granulated powder and the inductance requirements, the hot pressing method can be used, which requires less pressure during hot pressing and can better adhere the magnetic core and the conductor after hot pressing, and the required pressure is also smaller, but hot pressing will result in a decrease in pressing efficiency.
[0049] Preferably, the hot pressing pressure is ≧800Mpa / cm 2 For example, 800Mpa / cm 2 , 810Mpa / cm 2 , 820Mpa / cm 2 , 830Mpa / cm 2 , 840Mpa / cm 2 , 850Mpa / cm 2 , 860Mpa / cm 2 , 870Mpa / cm 2 , 880Mpa / cm 2 , 890Mpa / cm 2 or 900Mpa / cm 2 and more preferably 2000 MPa / cm 2 It is.
[0050] In the present application, since there is no restriction on the enameled wire, a higher density magnetic core can be obtained by using the molding pressure of the magnetic powder, and preferably, the pressure is 800Mpa / cm 2 and even exceed 2000MPa / cm 2The optimum pressure of the inductance can be selected according to the life of the die and the capacity of the press equipment.
[0051] Preferably, the hot pressing temperature is 90 to 180°C, and may be, for example, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, or 180°C, but is not limited to the recited values, and other unrecited values within the numerical range also apply.
[0052] Preferably, the hot pressing time is 5 to 100 s, and may be, for example, 5 s, 10 s, 20 s, 30 s, 40 s, 50 s, 60 s, 70 s, 80 s, 90 s, or 100 s, but is not limited to the recited values, and other unrecited values within the numerical range also apply.
[0053] Preferably, the heat treatment is an annealing treatment.
[0054] Preferably, the heat treatment process is carried out under a protective atmosphere.
[0055] Preferably, the gas used in the protective atmosphere is nitrogen and / or an inert gas.
[0056] Preferably, the heat treatment temperature is 650 to 850°C, and may be, for example, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 910°C, 920°C, 930°C, 940°C or 950°C, but is not limited to the recited numerical values, and other unrecited numerical values within the numerical range also apply.
[0057] Preferably, the heat treatment time is 30 to 50 minutes, and may be, for example, 30 minutes, 32 minutes, 34 minutes, 36 minutes, 38 minutes, 40 minutes, 42 minutes, 44 minutes, 46 minutes, 48 minutes, or 50 minutes, but is not limited to the listed numerical values, and other unlisted numerical values within the numerical range also apply.
[0058] In this application, the pressed green inductor is heat treated to densify the magnetic core, so as to obtain higher saturation magnetic flux density, higher magnetic permeability and lower loss, and to improve the strength of the inductor device. Different materials are selected for different heat treatment temperatures. For example, for amorphous metal soft magnetic powders such as FeSiB, FeSiBCr, FeNiSiBPC, the heat treatment temperature cannot exceed the crystallization temperature of the powder; for nanocrystalline gold soft magnetic alloy powders, the heat treatment temperature must be higher than the crystallization temperature but not higher than the grain growth temperature; the specific heat treatment temperature must be set according to the curve tested by differential scanning calorimeter; for gas atomized, or water atomized, or water and gas composite atomized, or multi-stage atomized soft magnetic powders such as FeSiAl, FeNi, FeNiMo, FeSi, etc., high temperature heat treatment must be selected according to the powder combination, and the heat treatment temperature must be higher than 650°C and lower than 850°C. During the heat treatment, inert gas protection such as nitrogen, argon, etc. may be used, or reducing gas protection such as hydrogen, hydrogen / nitrogen mixed gas, etc. In the present application, a conductor without enameled wire is used, and the conductor shape is I-shaped, S-shaped, L-shaped, U-shaped, W-shaped, E-shaped, etc., so that there is no contact between the conductors, and there is no problem of short circuit between the conductors.
[0059] In a second aspect, the present application provides a co-fired inductor manufactured by the manufacturing method described in the first aspect, the co-fired inductor including a magnetic core and at least one conductive wire located inside the magnetic core, the magnetic core including at least two magnetic powder layers sequentially stacked, the types of magnetic powder used in two adjacent magnetic powder layers being different, the conductive wire being located in one of the magnetic powder layers, both ends of the conductive wire extending from the magnetic core, and the portion of the conductive wire extending from the magnetic core being bent and then in close contact with an outer wall of the magnetic core.
[0060] In a preferred technical solution of the present application, the conductor wire is a bare wire without an enameled wire.
[0061] Preferably, the conductor wire is a copper wire.
[0062] Preferably, the conductor is a flat conductor having a rectangular cross section.
[0063] Preferably, the conductor wire is a straight conductor wire or a shaped conductor wire.
[0064] Preferably, the shape of the irregular conductor includes an S-shape, an L-shape, a U-shape, a W-shape or an E-shape.
[0065] Preferably, the conductor wires are arranged side by side on a horizontal plane at intervals within one layer of magnetic powder.
[0066] Compared with the prior art, the beneficial effects of the present invention are as follows: The manufacturing method of the present application uses a one-piece molding process to manufacture the inductor, avoiding the assembly process of excessive parts, and heat treatment after one-piece molding to fully release stress and reduce the hysteresis loss of the material, and the loss of the device is reduced under light load conditions, so that there is no extra gap between the conductor and the magnetic core, and the air gap is uniformly distributed in the magnetic core, reducing the vibration noise of eddy current loss. In addition, in the pressing process, different powders are added in a multi-batch addition manner to minimize the deformation of the conductor during the pressing process, improve the anti-windup ability of the magnetic core material, fully exert the respective advantages of different magnetic powder materials, and better exert the characteristics of the device. The combination of soft magnetic materials with positive and negative temperature coefficients can effectively improve the temperature stability of the device.
[0067] Other aspects may be appreciated after reading and understanding the detailed description. [Brief description of the drawings]
[0068] [Figure 1] FIG. 2 is a structural schematic diagram of a co-fired inductor manufactured in Example 1 of the present application. [Diagram 2] FIG. 2 is a structural schematic diagram of a co-fired inductor manufactured in Example 2 of the present application. [Diagram 3] FIG. 2 is a structural schematic diagram of a co-fired inductor manufactured in Example 3 of the present application. [Figure 4] FIG. 1 is a structural schematic diagram of a co-fired inductor manufactured in Example 4 of the present application. [Diagram 5] FIG. 1 is a structural schematic diagram of a co-fired inductor manufactured in Example 5 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0069] In the description of this application, the orientations or positional relationships indicated by terms such as "center," "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inside," and "outside" are orientations or positional relationships shown based on the drawings, and are merely intended to facilitate and simplify the description of this application, and do not indicate or imply that the mentioned devices or elements must have a specific orientation and be configured and operated in a specific orientation, and therefore cannot be understood as limiting this application. In addition, terms such as "first" and "second" are merely for describing purposes, and cannot be understood as indicating or implying relative importance or implicitly specifying the number of the technical features indicated. Thus, the limitation of a feature such as "first" or "second" can explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "multiple" means two or more.
[0070] In the description of this application, the terms "provide," "connect," and "couple" should be understood in a broad sense unless otherwise clearly defined or limited, and may refer to, for example, a fixed connection, a removable connection or an integral connection, a mechanical connection, an electrical connection, a direct connection, an indirect connection via an intermediate medium, or internal communication between two elements. A person skilled in the art can understand the specific meaning of the above terms in this application according to the specific situation.
[0071] The technical solution of the present application will be further described below through specific embodiments with reference to the drawings.
[0072] Example 1 This embodiment provides a method for manufacturing an integral co-fired inductor, which includes the following steps: (1) Fill the cavity with 0.2g of first magnetic powder, place a rectangular cross-section flat copper wire 1 on the surface of the first magnetic powder after removing the enamel wire, both ends of the wire 1 extend from the cavity, the shape of the wire 1 is a straight wire 1, the length is 14mm, the width is 2.6mm, and the thickness is 0.3mm, oscillate the cavity, embed the wire 1 inside the first magnetic powder, flatten the first magnetic powder, then fill the cavity with 0.6g of second magnetic powder, oscillate the cavity, flatten the second magnetic powder, finally fill the cavity with 0.2g of first magnetic powder, oscillate the cavity, and flatten the first magnetic powder; (2) The magnetic powder filled in the cavity is pressed into a mold. The pressing method is hot pressing, and the hot pressing pressure is 300Mpa / cm 2 , The hot pressing temperature is 180 °C, and the hot pressing time is 30 s. (3) After molding, the magnetic core is obtained by annealing in a nitrogen atmosphere, the heat treatment temperature is 700°C, and the heat treatment time is 30 minutes. (4) The conducting wire 1 extending from the magnetic core is successively impregnated, sprayed, bent, and tin-plated to obtain a co-fired inductor with a size of 11.0 mm × 5.0 mm × 2.0 mm, where the impregnation process is vacuum impregnation, and the spraying liquid used in the spraying process is epoxy resin.
[0073] Here, the first magnetic powder in step (1) was produced using the following method. (a) Insulation coating: Dilute phosphoric acid with acetone, the mass ratio of phosphoric acid to acetone is 1:60, mix phosphoric acid and acetone and stir for 1 minute, then leave for 5 minutes to prepare for use, mix FeSi soft magnetic powder with D50=20μm and diluted phosphoric acid and stir for 30 minutes, bake at 90℃ for 1 hour to obtain phosphorized soft magnetic powder, (b) Secondary coating: The coating material and the soft magnetic powder obtained in step (c) are mixed and stirred for 40 minutes, the coating material is 2 wt% of the soft magnetic powder, and the coating material is phenolic resin; (c) Granulation: The secondary coated soft magnetic powder was granulated using a 40 mesh granulator, and dried after granulation was completed. The drying time was 2 hours. The dried soft magnetic powder was sieved through a 30 mesh sieve, and then dried at 50°C for 0.8 hours. After natural cooling, it was sieved through a 30 mesh sieve, and magnesium oxide was added to the sieved soft magnetic powder to obtain the first magnetic powder.
[0074] The second magnetic powder is manufactured using the same operational steps and process parameters as the first magnetic powder, the difference being that the soft magnetic powder used in step (a) is replaced by FeSiAl magnetic powder, which is similarly subjected to insulating coating, secondary coating and granulation processes to obtain the second magnetic powder, and the process parameters used in each operational step are completely the same.
[0075] As shown in Figure 1, the first magnetic powder, the second magnetic powder and the first magnetic powder in the cavity of the manufactured co-fired inductor are filled in sequence to form a first magnetic powder layer 2, a second magnetic powder layer 3 and a third magnetic powder layer 4, respectively, and the conductive wire 1 is located in the first magnetic powder layer 2. The manufactured co-fired inductor is subjected to an inductance characteristic test, and the initial inductance L(0A)=150nH, the saturation current 90A and the temperature rise current 85A are measured. An efficiency test is performed using a 12V-1V step-down circuit, and during the test, when the switching power supply frequency is 500kHz and the electronic load is 5A, the efficiency reaches 81.5%, and when the electronic load is 25A, the efficiency reaches 90.3%.
[0076] Example 2 This embodiment provides a method for manufacturing an integral co-fired inductor, which includes the following steps: (1) Fill the cavity with 0.3g of the first magnetic powder, oscillate the cavity, flatten the first magnetic powder, then fill with 0.5g of the second magnetic powder, place a flat copper wire 1 with a rectangular cross section on the surface of the second magnetic powder after removing the enamel wire, both ends of the wire 1 extend out of the cavity, the shape of the wire 1 is S-shaped, the length is 10mm, the width is 2.6mm, and the thickness is 0.30mm, oscillate the cavity, embed the wire 1 inside the second magnetic powder, flatten the second magnetic powder, and finally fill with 0.3g of the first magnetic powder, oscillate the cavity, and flatten the first magnetic powder; (2) The magnetic powder filled in the cavity is pressed into a mold. The pressing method is hot pressing, and the hot pressing pressure is 400Mpa / cm 2 , The hot pressing temperature is 180 °C, and the hot pressing time is 30 s. (3) After molding, the magnetic core is obtained by annealing in an inert atmosphere, the heat treatment temperature is 650°C, and the heat treatment time is 50 min. (4) The conducting wire 1 extending from the magnetic core is sequentially impregnated, sprayed, bent, and tin-plated to obtain a co-fired inductor with a size of 8.0 mm × 6.0 mm × 1.9 mm, where the impregnation process is vacuum impregnation, and the spraying liquid used in the spraying process is epoxy resin.
[0077] Here, the first magnetic powder in step (1) was produced using the following method. (a) Insulation coating: Dilute phosphoric acid with acetone, the mass ratio of phosphoric acid to acetone is 1:63, mix phosphoric acid and acetone and stir for 3 minutes, then leave for 6 minutes to prepare for use, mix FeNi soft magnetic powder and diluted phosphoric acid and stir for 40 minutes, bake at 95 ° C for 1.2 hours, and obtain a phosphorized soft magnetic powder; (b) Secondary coating: The coating material and the soft magnetic powder obtained in step (c) are mixed and stirred for 45 minutes, the coating material is 5 wt% of the soft magnetic powder, and the coating material is epoxy resin; (c) Granulation: The secondary coated soft magnetic powder was granulated using a 43 mesh granulator, and dried after granulation was completed. The drying time was 2.3 hours. The dried soft magnetic powder was sieved through a 35 mesh sieve, dried at 55°C for 1 hour, naturally cooled, and then sieved through a 35 mesh sieve. Lubricant powder was then added to the sieved soft magnetic powder to obtain the first magnetic powder.
[0078] The second magnetic powder is manufactured using the same operational steps and process parameters as the first magnetic powder, the difference being that the soft magnetic powder used in step (a) is replaced by FeSiAl magnetic powder, which is similarly subjected to insulating coating, secondary coating and granulation processes to obtain the second magnetic powder, and the process parameters used in each operational step are completely the same.
[0079] As shown in Figure 2, the first magnetic powder, the second magnetic powder and the first magnetic powder in the cavity of the manufactured co-fired inductor are filled in sequence to form the first magnetic powder layer 2, the second magnetic powder layer 3 and the third magnetic powder layer 4, respectively, and the conductive wire 1 is located in the second magnetic powder layer 3. The manufactured co-fired inductor is subjected to an inductance characteristic test, and the initial inductance L(0A)=160nH, the saturation current 95A and the temperature rise current 90A are measured. An efficiency test is performed using a 12V-1V step-down circuit, and during the test, when the switching power supply frequency is 500kHz and the electronic load is 5A, the efficiency reaches 81.6%, and when the electronic load is 25A, the efficiency reaches 90.6%.
[0080] Example 3 This embodiment provides a method for manufacturing an integral co-fired inductor, which includes the following steps: (1) Fill the cavity with 0.2g of first magnetic powder, oscillate the cavity, flatten the first magnetic powder, then fill 0.6g of second magnetic powder, oscillate the cavity, flatten the second magnetic powder, and finally fill 0.2g of the first magnetic powder, place a flat copper conductor 1 with a rectangular cross section on the surface of the first magnetic powder after removing the enamel wire, both ends of the conductor 1 extend out of the cavity, the shape of the conductor 1 is "w" shaped, the length is 18mm, the width is 2.8mm, and the thickness is 0.26mm, oscillate the cavity, embed the conductor 1 inside the first magnetic powder, and flatten the first magnetic powder; (2) The magnetic powder filled in the cavity is pressed into a mold. The pressing method is hot pressing, and the hot pressing pressure is 400Mpa / cm 2 , The hot pressing temperature is 180 °C, and the hot pressing time is 30 s. (3) After molding, the magnetic core is obtained by annealing in a nitrogen atmosphere, the heat treatment temperature is 690°C, and the heat treatment time is 40 minutes. (4) The conducting wire 1 extending from the magnetic core is successively impregnated, sprayed, bent and tin-plated to obtain a co-fired inductor with a size of 7.5 mm × 6.5 mm × 1.8 mm, where the impregnation process is vacuum impregnation, and the spraying liquid used in the spraying process is epoxy resin.
[0081] Here, the first magnetic powder in step (1) was produced using the following method. (a) Insulation coating: Phosphoric acid is diluted with acetone, and the mass ratio of phosphoric acid to acetone is 1:65. Phosphoric acid and acetone are mixed and stirred for 5 minutes, then left to stand for 8 minutes for preparation for use. Fe powder with D50=10μm is mixed with the diluted phosphoric acid and stirred for 50 minutes. After baking at 100℃ for 1.3 hours, a phosphorized soft magnetic powder is obtained. (b) Secondary coating: The coating material and the soft magnetic powder obtained in step (c) are mixed and stirred for 55 minutes, the coating material is 7 wt% of the soft magnetic powder, and the coating material is silicone resin; (c) Granulation: The secondary coated soft magnetic powder was granulated using a 50 mesh granulator, and dried after granulation was completed. The drying time was 2.5 hours. The dried soft magnetic powder was sieved through a 40 mesh sieve, and then dried at 63°C for 1.1 hours. After natural cooling, it was sieved through a 40 mesh sieve, and a release powder was added to the sieved soft magnetic powder to obtain the first magnetic powder.
[0082] The second magnetic powder is manufactured using the same operational steps and process parameters as the first magnetic powder, the difference being that the soft magnetic powder used in step (a) is replaced by FeSiAl magnetic powder, which is similarly subjected to insulating coating, secondary coating and granulation processes to obtain the second magnetic powder, and the process parameters used in each operational step are completely the same.
[0083] As shown in Figure 3, the first magnetic powder, the second magnetic powder and the first magnetic powder in the cavity of the manufactured co-fired inductor are filled in sequence to form a first magnetic powder layer 2, a second magnetic powder layer 3 and a third magnetic powder layer 4, respectively, and the conductive wire 1 is located in the third magnetic powder layer 4. An inductance characteristic test was performed on the manufactured co-fired inductor, and the initial inductance L(0A)=150nH, the saturation current 100A and the temperature rise current 90A were measured. An efficiency test was performed using a 12V-1V step-down circuit, and during the test, when the switching power supply frequency was 500kHz and the electronic load was 5A, the efficiency reached 80.8%, and when the electronic load was 25A, the efficiency reached 91.2%.
[0084] Example 4 This embodiment provides a method for manufacturing an integral co-fired inductor, which includes the following steps: (1) Fill the cavity with 0.2g of first magnetic powder, place a flat copper wire 1 with a rectangular cross section on the surface of the first magnetic powder after removing the enamel wire, both ends of the wire 1 extend from the cavity, the shape of the wire 1 is a straight wire 1, the length is 10mm, the width is 2.0mm, and the thickness is 0.36mm, oscillate the cavity, embed the wire 1 inside the first magnetic powder, flatten the first magnetic powder, then fill the cavity with 0.6g of second magnetic powder, oscillate the cavity, flatten the second magnetic powder, finally fill the cavity with 0.2g of third magnetic powder, oscillate the cavity, and flatten the third magnetic powder; (2) The magnetic powder filled in the cavity is pressed into a mold. The pressing method is cold pressing, and the cold pressing pressure is 500Mpa / cm 2 , The cold pressing temperature is 180℃, and the cold pressing time is 30s. (3) After molding, the magnetic core is obtained by annealing in a nitrogen atmosphere, the heat treatment temperature is 850°C, and the heat treatment time is 30 minutes. (4) The conducting wire 1 extending from the magnetic core is successively impregnated, sprayed, bent, and tin-plated to obtain a co-fired inductor with a size of 8.0 mm × 5.0 mm × 3.0 mm, where the impregnation process is vacuum impregnation, and the spraying liquid used in the spraying process is epoxy resin.
[0085] Here, the first magnetic powder in step (1) was produced using the following method. (a) Insulation coating: Dilute phosphoric acid with acetone, the mass ratio of phosphoric acid to acetone is 1:70, mix phosphoric acid and acetone and stir for 6 minutes, then leave for 10 minutes to prepare for use, mix FeNi powder with D50=10μm and the diluted phosphoric acid and stir for 60 minutes, bake at 110℃ for 1.5 hours to obtain a phosphorized soft magnetic powder, (b) Secondary coating: The coating material and the soft magnetic powder obtained in step (c) are mixed and stirred for 60 minutes, the coating material is 10 wt% of the soft magnetic powder, and the coating material is silicone resin; (c) Granulation: The secondary coated soft magnetic powder was granulated using a 60 mesh granulator, and dried after granulation was completed. The drying time was 3 hours. The dried soft magnetic powder was sieved through a 50 mesh sieve, and then dried at 70°C for 1.2 hours. After natural cooling, it was sieved through a 50 mesh sieve, and magnesium oxide auxiliary raw material was added to the sieved soft magnetic powder to obtain the first magnetic powder.
[0086] The second magnetic powder is manufactured using the same operational steps and process parameters as the first magnetic powder, the difference being that the soft magnetic powder used in step (a) is replaced with FeSiAl soft magnetic powder, which is similarly subjected to insulating coating, secondary coating and granulation processes to obtain the second magnetic powder, and the process parameters used in each operational step are completely the same.
[0087] The third magnetic powder is manufactured using the same operation steps and process parameters as the first magnetic powder, the difference being that the soft magnetic powder used in step (a) is replaced with FeSi soft magnetic powder with D50=20μm, which is similarly subjected to insulating coating, secondary coating and granulation to obtain the third magnetic powder, and the process parameters used in each operation step are completely the same.
[0088] As shown in Figure 4, the first magnetic powder, the second magnetic powder and the third magnetic powder in the cavity of the manufactured co-fired inductor are filled in sequence to form a first magnetic powder layer 2, a second magnetic powder layer 3 and a third magnetic powder layer 4, respectively, and the conductive wire 1 is located in the first magnetic powder layer 2. The manufactured co-fired inductor is subjected to an inductance characteristic test, and the initial inductance L(0A)=120nH, the saturation current 70A and the temperature rise current 65A are measured. An efficiency test is performed using a 12V-1V step-down circuit, and during the test, when the switching power supply frequency is 500kHz and the electronic load is 5A, the efficiency reaches 79.5%, and when the electronic load is 25A, the efficiency reaches 88.3%.
[0089] Example 5 This embodiment provides a method for manufacturing an integral co-fired inductor, which includes the following steps: (1) Fill the cavity with 0.2g of the first magnetic powder, place a flat copper wire 1 with a rectangular cross section on the surface of the first magnetic powder after removing the enamel wire, both ends of the wire 1 extend from the cavity, and the shape of the wire 1 is a straight wire 1 with a length of 14 mm, a width of 2.2 mm, and a thickness of 0.35 mm; oscillate the cavity to embed the wire 1 inside the first magnetic powder, flatten the first magnetic powder, and then fill 0.3g of the second magnetic powder, 0.5g of the third magnetic powder, 0.3g of the second magnetic powder, and 0.2g of the first magnetic powder in sequence, oscillate the cavity each time a magnetic powder is filled to flatten the surface of the magnetic powder; (2) The magnetic powder filled in the cavity is pressed into a mold. The pressing method is cold pressing, and the cold pressing pressure is 1600Mpa / cm 2 and (3) After molding, the magnetic core is obtained by annealing in a nitrogen atmosphere, the heat treatment temperature is 690°C, and the heat treatment time is 40 minutes. (4) The conducting wire 1 extending from the magnetic core is impregnated, sprayed, bent, and tin-plated in order, and then a co-fired inductor with a size of 10.0 mm × 5.0 mm × 2.0 mm (shown in Figure 1) is obtained, where the impregnation process is vacuum impregnation, and the spraying liquid used in the spraying process is epoxy resin.
[0090] Here, the first magnetic powder in step (1) was produced using the following method. (a) Insulation coating: Dilute phosphoric acid with acetone, the mass ratio of phosphoric acid to acetone is 1:65, mix phosphoric acid and acetone and stir for 5 minutes, then leave for 8 minutes to prepare for use, mix FeSi soft magnetic powder with D50=20μm and diluted phosphoric acid and stir for 50 minutes, bake at 100℃ for 1.3 hours to obtain phosphorized soft magnetic powder, (b) Secondary coating: The coating material and the soft magnetic powder obtained in step (c) are mixed and stirred for 55 minutes, the coating material is 7 wt% of the soft magnetic powder, and the coating material is phenolic resin; (c) Granulation: The secondary coated soft magnetic powder is granulated in a 50 mesh granulator, and dried after granulation is completed. The drying time is 2.5 hours. The dried soft magnetic powder is sieved through a 40 mesh sieve, and then dried at 63°C for 1.1 hours. After natural cooling, it is sieved through a 40 mesh sieve, and magnesium oxide is added to the sieved soft magnetic powder to obtain the first magnetic powder.
[0091] The second magnetic powder is manufactured using the same operating steps and process parameters as the first magnetic powder, the difference being that the soft magnetic powder used in step (a) is replaced with FeNi soft magnetic powder with D50=10 μm, which is similarly subjected to insulating coating, secondary coating and granulation to obtain the second magnetic powder, and the process parameters used in each operating step are completely the same.
[0092] The third magnetic powder is manufactured using the same operation steps and process parameters as the first magnetic powder, the difference being that the soft magnetic powder used in step (a) is replaced by FeSiAl magnetic powder, which is similarly subjected to insulating coating, secondary coating and granulation processes to obtain the third magnetic powder, and the process parameters used in each operation step are completely the same.
[0093] As shown in FIG. 5, the first magnetic powder, the second magnetic powder, the third magnetic powder, the second magnetic powder and the first magnetic powder in the cavity are filled in sequence in the manufactured co-fired inductor to form the first magnetic powder layer 2, the second magnetic powder layer 3, the third magnetic powder layer 4, the fourth magnetic powder layer 5 and the fifth magnetic powder layer 6, respectively, and the conductor 1 is located in the first magnetic powder layer 2. The manufactured co-fired inductor is subjected to an inductance characteristic test, and the initial inductance L(0A)=165nH, the saturation current 105A and the temperature rise current 90A are measured. An efficiency test is performed using a 12V-1V step-down circuit, and during the test, when the switching power supply frequency is 500kHz and the electronic load is 5A, the efficiency reaches 82.0%, and when the electronic load is 25A, the efficiency reaches 91.5%.
[0094] Comparative Example 1 This embodiment provides a method for manufacturing an integral co-fired inductor, which includes the following steps: (1) 1 g of magnetic powder is filled into the cavity, and a flat copper conductor 1 having a rectangular cross section is embedded in the magnetic powder after removing the enamel wire, and the shape of the conductor 1 is a straight conductor 1, with a length of 14 mm, a width of 2.6 mm, and a thickness of 0.3 mm. (2) The magnetic powder filled in the cavity is pressed into a mold. The pressing method is hot pressing, and the hot pressing pressure is 400Mpa / cm 2 , The hot pressing temperature is 160 °C, and the hot pressing time is 25 s. (3) After molding, the magnetic core is obtained by annealing in a nitrogen atmosphere, the heat treatment temperature is 700°C, and the heat treatment time is 30 minutes. (4) The conducting wire 1 extending from the magnetic core is successively impregnated, sprayed, bent, and tin-plated to obtain a co-fired inductor with a size of 11.0 mm × 5.0 mm × 2.0 mm, where the impregnation process is vacuum impregnation, and the spraying liquid used in the spraying process is epoxy resin.
[0095] Here, the magnetic powder in step (1) was produced using the following method. (a) Insulation coating: Dilute phosphoric acid with acetone, the mass ratio of phosphoric acid to acetone is 1:60, mix phosphoric acid and acetone and stir for 1 minute, then leave for 5 minutes to prepare for use, mix FeSi soft magnetic powder with D50=20μm and diluted phosphoric acid and stir for 30 minutes, bake at 90℃ for 1 hour to obtain phosphorized soft magnetic powder, (b) Secondary coating: The coating material and the soft magnetic powder obtained in step (c) are mixed and stirred for 40 minutes, the coating material is 2 wt% of the soft magnetic powder, and the coating material is phenolic resin; (c) Granulation: The secondary coated soft magnetic powder was granulated using a 40 mesh granulator, and dried after granulation was completed. The drying time was 2 hours. The dried soft magnetic powder was sieved through a 30 mesh sieve, and then dried at 50°C for 0.8 hours. After natural cooling, it was sieved through a 30 mesh sieve, and magnesium oxide auxiliary raw material was added to the sieved soft magnetic powder to obtain the magnetic powder.
[0096] An inductance characteristic test was performed on the manufactured co-fired inductor, and the initial inductance L(0A)=140nH, saturation current 50A, and temperature rise current 40A were measured. An efficiency test was performed using a 12V-1V step-down circuit, and during the test, when the switching power supply frequency was 500kHz and the electronic load was 5A, the efficiency reached 82.3%, and when the electronic load was 25A, the efficiency reached 88.3%. [Explanation of symbols]
[0097] 1 - conductor; 2 - first magnetic powder layer; 3 - second magnetic powder layer; 4 - third magnetic powder layer; 5 - fourth magnetic powder layer; 6 - fifth magnetic powder layer.
Claims
1. A method for manufacturing an integral co-fired inductor, the method includes filling a cavity with magnetic powder in a batch, the magnetic powder in two adjacent layers is different in type, embedding at least one conductive wire in one of the magnetic powder layers, and causing both ends of the conductive wire to extend from the cavity, and then sequentially pressing and heat treating the magnetic core to obtain the conductive wire extending from the magnetic core, bending the conductive wire extending from the magnetic core, and tinning the conductive wire to obtain the co-fired inductor, The magnetic powder is produced by a method in which soft magnetic powder is successively subjected to an insulating coating, a secondary coating and a granulation process, and then the magnetic powder is obtained; The conductor is a bare wire without an enameled wire, and the shape of the conductor is a deformed conductor, and the shape of the deformed conductor includes an S-shape, an L-shape, a U-shape, a W-shape, or an E-shape; The method is characterized in that the heat treatment process is carried out under a protective atmosphere, the gas used in the protective atmosphere is nitrogen and / or an inert gas, and the heat treatment temperature is 650 to 850°C.
2. 2. The method according to claim 1, wherein the soft magnetic powder comprises FeSiCr, FeSi, FeNi, FeSiAl, carbonyl-based iron powder, carbonyl iron-nickel powder, FeNiMo, Fe-based amorphous nanocrystalline material, Co-based amorphous nanocrystalline soft magnetic material, or Ni-based amorphous nanocrystalline soft magnetic material.
3. The manufacturing method described in claim 1 or 2, characterized in that the coating process used in the insulating coating includes phosphorization, acidification, oxidation or nitridation.
4. The coating process used in the insulating coating uses a phosphorization treatment to insulate the soft magnetic powder, The phosphorization treatment includes mixing the soft magnetic powder with diluted phosphoric acid, stirring, and baking to obtain a phosphorized soft magnetic powder; Dilute the phosphoric acid with acetone, The mass ratio of the phosphoric acid to acetone is 1:(60-70), The phosphoric acid and acetone are mixed and stirred for 1-6 minutes, then allowed to stand for 5-10 minutes before use. The soft magnetic powder is mixed with the diluted phosphoric acid and stirred for 30 to 60 minutes. The baking temperature is 90 to 110° C. The method according to claim 3, wherein the baking time is 1 to 1.5 hours.
5. The secondary coating includes mixing and stirring the coating material and the insulating coated soft magnetic powder; The coating material is 2 to 10 wt % of the soft magnetic powder, the coating material comprises a phenolic resin, an epoxy resin, or a silicone resin; The method according to any one of claims 1 to 4, characterized in that the coating material and the soft magnetic powder are mixed and stirred for 40 to 60 minutes.
6. The granulation process includes granulating the soft magnetic powder with the secondary coating, and then drying, drying and cooling the powder after the granulation is completed to obtain the magnetic powder. The granulation process is carried out in a granulator with 40 to 60 mesh. The drying time is ≦3 h, The dried soft magnetic powder is sieved through a 30 to 50 mesh sieve and then dried. The drying temperature is 50 to 70° C. The drying time is 0.8 to 1.2 h, The cooling process is natural cooling, The cooled soft magnetic powder is sieved through a 30 to 50 mesh sieve, and then auxiliary raw materials are added to the sieved soft magnetic powder to obtain the magnetic powder; The manufacturing method according to any one of claims 1 to 5, characterized in that the auxiliary raw material includes magnesium oxide, a lubricant powder, or a release powder.
7. Filling the cavity with the first magnetic powder, the second magnetic powder, and the first magnetic powder in three batches in sequence; The method according to any one of claims 1 to 6, characterized in that the conductive wire is embedded in a second magnetic powder.
8. The conductor is a copper wire, The conductor is a flat conductor having a rectangular cross section, The manufacturing method according to any one of claims 1 to 7, characterized in that the conductive wires are arranged side by side on a horizontal plane at intervals and laid inside one layer of the magnetic powder.
9. The pressing method is hot pressing or cold pressing, The hot pressing pressure is ≧800 MPa; The hot pressing temperature is 90 to 180° C. The hot pressing time is 5 to 100 s, the heat treatment is an annealing treatment, The method according to any one of claims 1 to 8, wherein the heat treatment time is 30 to 50 minutes.
10. A co-fired inductor manufactured by the manufacturing method according to any one of claims 1 to 9, the co-fired inductor including a magnetic core and at least one conductor wire located inside the magnetic core, the magnetic core including at least two magnetic powder layers sequentially stacked, the types of magnetic powder used in the adjacent two magnetic powder layers being different, the conductor wire being located in one of the magnetic powder layers, both ends of the conductor wire extending from the magnetic core, the conductor wire portion extending from the magnetic core being bent and then in close contact with an outer wall of the magnetic core, A co-fired inductor, characterized in that the conductor wire is a bare wire without an enameled wire, and the shape of the conductor wire is a deformed conductor wire, and the shape of the deformed conductor wire includes an S-shape, an L-shape, a U-shape, a W-shape, or an E-shape.
11. The conductor is a copper wire, The conductor is a flat conductor having a rectangular cross section, 11. The co-fired inductor of claim 10, wherein the conductive wires are laid inside one layer of magnetic powder at intervals side by side on a horizontal plane.
Citation Information
Patent Citations
Iron powder core magnetic device
JP1985001816A
Manufacture of magnetic powder for dust core
JP1997320830A
Phosphate-coated iron powder and method of making same
JP2000504785A
Powder magnetic core and manufacturing method of the same
JP2005268685A
Dust core and manufacturing method thereof
JP2006024869A
